Megawati Presidential Political - Indah Rizki Aruma Nurjannah; Nurul Umamah; Marjono Marjono (JURNAL HISTORICA, 2018)
President Megawati is the fifth president of a unitary state of the republic of Indonesia, during his reign has issued a political policy, both domestic and foreign political policy. The problems in this research are; (1) how was Megawati in the political stage before becoming president of the republic of Indonesia in 2001, (2) how was Megawati's domestic and foreign policy politics of 2001-2004 ?, (3) how was the impact of domestic and foreign policy of President Megawati Year 2001-2004 ?. The purpose of this study is 1. To analyze the involvement of Megawati in the Indonesian political scene in 2001, 2. To analyze domestic and foreign policy of President Megawati in 2001-2004, 3. To analyze the impact of domestic and foreign political policy President Megawati Year 2001-2004. The research method used is historical research method. The conclusion of this research is Megawati's involvement in the Indonesian political stage, becoming the fifth president and issuing domestic and foreign political policies that have an impact on the political, social and economic aspects of Indonesia. Keywords: Megawati, Political Policy.